Development of nutrient management system based on ion-equivalent concentration ratio and ion monitoring to maintain ionic balance in closed hydroponic solution - Gang, MinSeok; Kim, Hak-Jin; Ahn, Tae In; Cho, Woo-Jae; Lee, Sang-Hyun; Lee, Ju Young; Hwang, Ji-Eun (Elsevier BV, 2025)
An automated nutrient management system was developed to maintain the ionic balance in the reused nutrient solution in a closed-loop hydroponics system. Fertilizers were supplied with variable compositions, using a replenishment algorithm based on electrical conductivity (EC) and ion-equivalent concentration ratio monitored with ion-selective electrodes (ISEs). An array of NO3？, K+, and Ca2+ electrodes was fabricated to measure ion concentrations in the drained solution. The measured ion concentrations were converted into ion-equivalent concentration ratios and fed back for adaptive control to determine the fertilizer composition. The system adjusted the fertilizer composition twice a week, using fertilizers (Ca(NO3)2·4H2O, KH2PO4, KNO3, NH4NO3, MgSO4·7H2O, K2SO4) and an acid solution (H3PO4) for pH adjustment. The fertilizer volumes were calculated using nonlinear programming methods based on the fertilizer compositions. The system activated each dosing channel differently to introduce fertilizers into the mixing tank. The system’s performance was tested by growing lettuce (Lactuca sativa L.) in a greenhouse. The measured ion concentrations were compared with the results of chemical analysis, and the actual ion-equivalent concentration ratios of the drained solution were compared to the target ratio of a standard Hoagland solution. The root mean square errors (RMSEs) of NO3？, K+, and Ca2+ measurements using ISEs were 39.18 mg L？1, 17.79 mg L？1, and 20.64 mg L？1, respectively. The RMSE of the target ratios on the last day of cultivation was 5.9 %, representing a 58 % improvement compared to the system based on only EC. Therefore, the developed system may complement the conventional EC-based system for closed hydroponics.